Repetition as Rhetorical Strategy in the English Translation of Surah Al-Mursalat: A Stylistic and Discourse Analysis - M. Asril Marpaung (Journal Of Global Research Publications, 2025)
This study investigates the rhetorical and discourse functions of repetition in the English translation of Surah Al-Mursalat by M.A.S. Abdel Haleem, focusing on the refrain “Woe on that Day to those who denied the truth.” Using a qualitative descriptive method grounded in stylistics and discourse analysis, the study explores how this fixed phrase, repeated ten times across the chapter, operates at multiple linguistic levels. The analysis reveals that the refrain serves three interrelated functions: stylistically, it foregrounds divine warning and creates rhythmic cohesion; structurally, it segments the surah into thematic units and signals discourse boundaries; rhetorically, it intensifies condemnation and engages the reader emotionally through cumulative repetition. Abdel Haleem’s consistent rendering of the refrain retains these functions effectively, unlike other translations that introduce lexical variation. The findings demonstrate that repetition in Qur’anic translation is not merely ornamental but performs essential linguistic and communicative roles. This study contributes to Qur’anic stylistics, translation studies, and discourse analysis by showing that sacred texts, when translated with rhetorical sensitivity, can preserve the stylistic integrity of the original.